ASSERTIVE COMMUNICATION TO IMPROVE INTERPERSONAL COMMUNICATION IN THE SURABAYA ARSA COMMUNITY (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
Interpersonal communication within the group becomes an important factor in achieving group goals. From the results of the needs analysis, it was known that interpersonal communication faced by service partner groups was rooted in assertive communication skills. For this reason, assertive communication training was chosen in service activities to improve the knowledge, attitudes, and skills of service partner groups. This community service partner was the “Arsa Community”, with 10 participants. The training was designed as psychoeducation using lecturing methods, giving modules, and online discussions. Data were collected using questionnaires, observations, and interviews. The data were analyzed quantitatively and qualitatively. The results showed that quantitatively, psychoeducation could significantly improve the knowledge, attitudes, and assertive communication skills of service partners. Furthermore, qualitatively it was known that Arsa Community’s members understood much more about the importance of interpersonal communication skills after attending this psychoeducation. The results of this community service were discussed to achieve a more comprehensive perspective in doing as well as choosing several media in community service.